Tell me your date of birth, and I will tell you how good you are in orienteering - Ferriz-Valero, Alberto; Montiel-Bontmatí, Javier; Østerlie, Ove; Caraça-Valente, Juan Pedro; Mínguez-Viñambres, Alberto; Esteve-Ibáñez, Héctor (Frontiers in Sports and Active Living, 2025)
Orienteering is a sport where participants must choose the best route between control points marked on the map, combining it with their displacement capacity. It combines endurance running with mental capacity. As in other sports, age can be a determinant in defining differences among youth runners. In this research, the hypothesis is that older orienteers will show better performance than younger orienteers within the same competitive group, for both girls and boys. Overall, official results of the FEDO (Spanish Federation of Orienteering) in long and middle-distance events, from 2005 to 2023, have been analyzed (sprint format events were excluded). Different categories from ten to twenty years of age for both sexes were included, and each category was divided into two years (1Y, 2Y) and two semesters (1S, 2S) within each year, creating four independent variables from the combination of year and semester (1Y1S, 1Y2S, 2Y1S, and 2Y2S). A total of 7,731 entries were examined, 4,318 were boys and 3,109 were girls. Descriptive statistics were analyzed for each variable, showing the mean and standard deviation. Normal distribution was confirmed for all variables (p > 0.05). Results showed a significant performance difference in favor of older orienteers in the youngest categories (U-10, M/F-12, M/F-14, and M-16), with these differences disappearing as age and performance increased (M/F-18 and M/F-20). These findings support the research hypothesis and align with other studies where age-related differences have also been found in other sports.